The influence of anthropomorphism on children's learning and attitudes toward snakes - Reider, Lori Beth; LoBue, Vanessa (Frontiers in Developmental Psychology, 2024)
Introduction Previous research suggests that negative input contributes to children's fear development, while more positive input can reduce children's fear. The current study examined whether using anthropomorphic input can alter children's learning and attitudes toward snakes in ways that may promote more positive attitudes toward a commonly feared animal. Methods Children from the United States (N = 89; Mage = 5.43 years; 47 females, 42 males) reported their baseline knowledge and fear of snakes. Children then heard a story about a snake that did (n = 44) or did not (n = 45) contain anthropomorphic information. Following the story, children answered questions about their fear of snakes, knowledge acquired from the story, willingness to attribute anthropomorphic qualities to snakes, and willingness to help snakes. Results and discussion After hearing either story, children reported less fear of snakes. Further, while children in the anthropomorphic condition were more likely to attribute anthropomorphic qualities to snakes, there were no differences in the amount of information children learned. Most importantly, children in the anthropomorphic condition prioritized helping snakes more than children in the neutral condition. These findings demonstrate the impact of anthropomorphic information on children's attitudes and learning, and highlight the ways in which altering the input children receive may impact their learning and attitudes toward living creatures.